Lehninger principles of biochemistry - Lehninger, Albert L.; Nelson, David L. (David Lee), 1942-; Cox, Michael M.; Hoskins, Aaron A. (Macmillan Learning, 2021)
"Lehninger Principles of Biochemistry earned acclaim for its presentation and organization of complex concepts and connections, anchored in the principles of biochemistry. This legacy continues in the eighth edition with a new framework that highlights the principles and supports student learning"--